An Implementation of Guided Discovery Learning on Bioprocess in Cells Material to Improve Learning Outcomes - Utami, Anisa Dyah; Susanti, R. (Journal of Biology Education, 2020)
Bioprocess in cells consists of membrane transport, protein synthesis and cell reproduction. Material cannot be understood if only looking at pictures because the material is about a complex process contained in a cell. Practicum and animation video are learning media that can be used to help students visualize the material. Guided discovery learning helps students to construct their own knowledge gained by being actively involved in the learning process of practicum and animation video. This study aims to determine the effectiveness of guided discovery learning of bioprocess material in cells on student learning outcomes. Research methods is Pre-Experimental Design using One-Group Pretest Posttest. The results showed that 100% of students 'psychomotor learning outcomes were good, students' cognitive learning outcomes> 80% of students obtained grades score 70 and N gains were in the medium category. It can be concluded that learning bioprocess material in cells using guided discovery learning is an effective way to improve student learning outcomes.